When Accent Does Not Match Expectations: A Dynamic Perspective of L2 Speaker Evaluations in a French Interview Context - Lindberg, Rachael; Trofimovich, Pavel (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2023)
According to expectation violation theory, job applicants can be upgraded or downgraded during an interview when their accent does not match employers’ speech expectations. Focusing on the employment of second language French job candidates in Québec, this study explored this issue dynamically in terms of how expectations may impact the trajectory of interview evaluations. Participants included 60 Québec French raters and 6 female job candidates applying to a waitress or pizza cook position, presented through their resumes as either first (L1) or second (L2) language French speakers. Each speaker’s interview audios were presented to raters in expectancy-congruent and expectancy-incongruent scenarios. Raters first provided resume-based employability assessments, then two more evaluations throughout a typical sequence of interview questions. The congruent and incongruent scenarios revealed similar evaluation patterns, where the L2 French cook applicant’s employability improved after initially being downgraded. Implications are discussed regarding listeners’ readjustment of their perceptions following first-impression biases.